THE PEMBERIAN CONTRAX RELAX EXERCISE PADA INTERVENSI PEMBERIAN SHORT WAVE DIATHERMY (SWD), TRANSCUTANEUS ELECTRICAL NERVE STIMULATION (TENS), DAN MASSAGE MENURUNKAN NYERI PADA CERVICAL SPONDYLOSIS DI RSUD BADUNG - I Made Agus Arta Winangun (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2013)
Cervical spondylosis is the formation of osteophytes on the edge of the cervical spine caused by reduced elasticity discus. Pain due to spasm is one of the perceived clinical manifestations in patients with cervical spondylosis. The research was conducted in Badung District Hospital Physiotherapy Clinic. This research is experimental, randomized design with pre test and post test control group design. Samples obtained by 20 people consisting of 10 persons of control group and 10 treatment groups. The sample was selected by randomized sampling technique. Independent variables in this study is the SWD, TENS, massage and contrax relax exercise therapy.Dependent variable is the change in pain intensity as measured by the VAS scale. Data were analyzed with parametric statistical test with t test. The results obtained t value of 42.69 with an average difference of 64.30, p of 0.00 (p <0.05) results showed that mean H0 rejected SWD, TENS and massage therapy effectively reduce pain in cervical spondylosis . In the intervention SWD, TENS, massage and contrax relax exercise obtained t value of 38.03, an average of 70.40, p of 0.00 (p <0.05) indicates that the SWD, TENS, massage and contrax relax exercise therapy effectively reduce pain intensity exercise.From the results showed no significant difference in the effect of therapeutic interventions in which the SWD, TENS, massage and contrax relax exercise more effective to reduce the pain away, because the research results obtained from the average difference in pain intensity decreased by 70.40 while in SWD, TENS and massage intervention gained an average decrease in pain intensity difference of 64,30.